Regularisation problems at the determination of the acoustic power of sound sources - Piechowicz, J. (Archives of Acoustics, 2006)
This paper presents exploratory problems of regularisation of the inverse method for theinvestigation of the characteristics of acoustic sources at industrial conditions. The solutionof problem is to find an effective method for the determination of optimal regularisation parametersin acoustic inverse problems. The sound power of the sound source distribution canbe simply deduced from the measured pressure field and the inversion of the correspondingmatrix of frequency response functions. The accuracy of reconstruction of the sound power ofthe source is crucially dependent on the conditioning of the matrix to be inverted. The successof regularisation depends on the appropriate choice of the regularisation parameter.